Pan-cancer analysis identified CD248 as a potential target for multiple tumor types - Guo, Li; Liao, Yan; Zhang, Xuyang; Guo, Rongjuan; Wang, Zheng; Yang, Deqin (Frontiers in Pharmacology, 2025)
ObjectiveTumors remain a major cause of death worldwide due to late-stage presentation and late diagnosis. Cell therapies have revolutionized the landscape in the precision treatment of tumors. However, there are still many challenges that limit the therapeutic efficacy. Additionally, cancer treatment also entails a major financial burden throughout the entire phase, making it preferable to find a specific biomarker for the early prognosis of the tumor.MethodsIn this study, the role of CD248 in pan-cancer was analyzed through diverse tumor-associated databases, such as the Human Protein Atlas Database, the GEPIA2 Database, the cBioPortal Database, the TIMER Database, the STRING tool, and so on. In addition, CD248 mRNA and protein levels were assessed in a series of head and neck squamous cell carcinoma (HNSC) cell lines using qRT-PCR and Western blot. Furthermore, siCD248 was used to detect the effect of CD248 on the invasion, migration, and proliferation of HNSC cells by transwell assay, scratch wound healing assay, and EdU assay, respectively.ResultsCD248 expression was significantly increased and correlated with advanced stage and poor prognosis in various tumors. Genetic alterations of CD248 were also associated with a poor prognosis of patients. Single-cell sequencing revealed that CD248 was mainly expressed on fibroblasts within the stroma, and its expression was positively correlated with the infiltration of immune cells in tumors. In addition, CD248 interacted with 11 common tumor biomarkers. Experiment results indicated that CD248 mRNA and protein expression were upregulated in HNSC cell lines, and inhibition of CD248 suppresses the invasion, migration, and proliferation of HNSC cells.ConclusionHigh CD248 expression played a crucial role in pan-cancer, including immune cell infiltration, tumor progression and metastasis, and patient prognosis. CD248 plays a crucial role in tumor cells’ functions, including invasion, migration, and proliferation. All these findings indicated that CD248 may be a novel oncoprotein and a potential therapeutic target for pan-cancer.